Application of SAS for analysis of data of medical institutions from data.egov.kz portal (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
Abstract. The article discusses the statistical analysis of medical data on the example of infectious diseases using SAS. The initial data for the research were taken from the open source data.egov.kz, which presents the latest information on infectious diseases in 3 regions and 1 city of the Republic of Kazakhstan. The methodology is based on the use of methods of descriptive statistics, graphical data analysis, building models on the SAS platform and can be used for a more in-depth analysis of infectious diseases in various population groups, as well as for their description in the cities of Kazakhstan. During the research, statistics were obtained using the SAS system for the level of infectious morbidity and the downloaded data was visualized in the form of various diagrams. The information obtained on the level and nature of infectious diseases can be used to assess trends in the health status of the population, plan various types of specialized medical care and treatment and preventive measures, and make rational use of the material and human resources of the healthcare system.
Keywords: data analysis; SAS platform; open source; infectious diseases; model